2017
DOI: 10.1039/c7ra01449j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the acceptor pattern and substitution position on the properties of N-phenyl-carbazolyl based donor–acceptor–donor molecules

Abstract: Four D–A–D type molecules were designed and synthesized, and their specific properties including optical, redox and thermal stabilities were studied in detail. The influence of substitution and the heteroatom effects were also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…In fact, the efficiency of 0.85 Cd/A was comparable with the typical results for solution-processed OLEDs based on fluorescent small molecules [ 25 , 26 ]. The schematic diagram of the structures of OLEDs and the energy levels of the materials is shown in Figure 7 d. In [ 27 ], the spectral properties of a series of similar compounds with a carbazole donor were investigated. All compounds based on thiadiazole and selenadiazole were characterized by luminescence in the range of 500–600 nm.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the efficiency of 0.85 Cd/A was comparable with the typical results for solution-processed OLEDs based on fluorescent small molecules [ 25 , 26 ]. The schematic diagram of the structures of OLEDs and the energy levels of the materials is shown in Figure 7 d. In [ 27 ], the spectral properties of a series of similar compounds with a carbazole donor were investigated. All compounds based on thiadiazole and selenadiazole were characterized by luminescence in the range of 500–600 nm.…”
Section: Resultsmentioning
confidence: 99%
“…37−39 Undeuterated BT-2PhCz was also synthesized as a comparison, whose electroluminescence had not been studied in previous reports. 40…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the mentioned structural features, it has been reported that several fluorophores and some DSEgens have Donor-Acceptor (DÀ A) or Donor-Acceptor-Donor (DÀ AÀ D) architectures. [5][6][7] This is a recurring design that helps to change the emission of the compounds by tuning their bandgap. [8] From the numerous reported DÀ A and DÀ AÀ D compounds, we noted that the heterocycle thiazole has been scarcely incorporated as the acceptor fragment, compared to other heterocycles like benzothiadiazole.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the mentioned structural features, it has been reported that several fluorophores and some DSEgens have Donor‐Acceptor (D−A) or Donor‐Acceptor‐Donor (D−A−D) architectures [5–7] . This is a recurring design that helps to change the emission of the compounds by tuning their bandgap [8] .…”
Section: Introductionmentioning
confidence: 99%